Enzyme-linked immunosorbent assay for detection and quantitation of capsular antigen of Haemophilus influenzae type b. - Crosson, F J (1978)
An enzyme-linked immunosorbent assay was developed to detect the presence of the ribose-ribitol phosphate capsular antigen of Haemophilus influenzae type b in laboratory and clinical specimens. The assay is simple, sensitive, specific, and quantitative and should prove to be of value in the diagnosis and management of H. influenzae infections.